Bodyweight threshold for sudden onset of ketosis might exist in ketosis‐prone type 2 diabetes patients. Issue 2 (14th August 2019) - Satomura, Atsushi; Oikawa, Yoichi; Haisa, Akifumi; Inoue, Ikuo; Noda, Mitsuhiko; Shimada, Akira
Abstract: Ketosis‐prone type 2 diabetes is recognized as atypical diabetes. These patients are often male, characterized by obesity, sudden onset of ketosis and a transient decrease in insulin secretion capacity that can be recovered with temporal insulin therapy. Here, we report a male patient with ketosis‐prone type 2 diabetes who was followed up for 8 years. During the follow‐up period, his bodyweight fluctuated and he experienced four episodes of critical ketosis recurrence in association with bodyweight gain. He discontinued insulin therapy after each ketosis episode within the first 4 years, but thereafter, he had to continue insulin therapy because of decreased insulin secretion capacity. Interestingly, his peak bodyweight just before the repeated ketosis episode gradually decreased, and the insulin secretion capacity after the recovery from repeated ketosis decreased in parallel with his peak bodyweight. This long‐term clinical course might be a clue to understand the pathophysiology of ketosis‐prone type 2 diabetes. Abstract : We report a male patient with ketosis‐prone type 2 diabetes who was followed up for 8 years. During the follow‐up period, his bodyweight fluctuated, and the ketosis episodes recurred four times in association with bodyweight gain. Interestingly, his peak bodyweight just before the repeated ketosis episode gradually decreased, and the insulin secretion capacity after the recovery from repeated ketosis decreased in parallel with his peak bodyweight; this long‐term clinical course might be one of the characteristics of ketosis‐prone type 2 diabetes.